Empowering Seventh-day Adventist Church Communities through Servant Leadership: Biblical Lessons From Mark 10:43-45 - Tan, Leonard Valwen (Fakultas Filsafat Universitas Advent Indonesia, 2025)
This study explores the biblical and theological foundations of servant leadership as revealed in Mark 10:43-45 and examines its application within the Seventh-day Adventist Church. Rooted in the teachings of Jesus Christ, servant leadership presents a countercultural model of authority centred on humility, love, and sacrifice. The research integrates biblical exegesis with theological reflection, emphasizing how the principles of servant leadership are affirmed and expanded through the writings of Ellen G. White, particularly in her discussions on character formation, spiritual influence, and the ministry of the Holy Spirit. Utilizing an applied theology methodology, this paper analyses how Christ’s paradigm of leadership can strengthen spiritual growth, increase member participation, and promote sustainable community development within the Adventist context. The study concludes that servant leadership, when faithfully practiced, transforms not only organizational structure but also the spiritual DNA of the church—turning it into a living reflection of Christ’s humility and selfless love.